Acicular martensite induced superior strength-ductility combination in a 20Cr2Ni2MoV steel - Wang, Y.L.; Shen, Y.F.; Jia, N.; Wang, J.J.; Zhao, S.-X. (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2022)
The super combination of ultrahigh strength and good ductility is in high demand for the gear steels. Here we improved the mechanical properties of a micro-alloyed gear steel through the fabrication route composed of carburizing and re-quenching. The results showed that the different re-quenching temperatures significantly affect not only the sizes and morphologies of precipitates and martensite but also the ratio of low-angle grain boundaries to high-angle grain boundaries as well as dislocation densities. The maximum ultimate tensile strength up to 2420 MPa was obtained after re-quenching at 780 °C, while the steel re-quenched at 820 °C exhibited the highest yield strength of 1500 MPa despite of the decreased ultimate tensile strength of 2145 MPa. Especially, a good ductility of 8.5% was maintained in the carburized steel processed after 780 °C re-quenching. The spherically nanosized precipitates together with the high ratio of low-angle grain boundaries were beneficial for the simultaneously improved strength and ductility.